The Influence of Brand Image (Image Mere K) on Case Study Consumer Buying Interest in the Saladbros Restaurant, Bali - Nasution, Iga Yohana; Lidia Yunita (Journal of Economics and Business (JECOMBI), 2022)
The more developed the economy of a nation, the higher the competition between business actors in controlling the market. Unique and creative branding can build a positive brand image and is one strategy to compete. Promotion is an important factor in realizing a company's sales goals. In order for consumers to be willing to become customers, they must first be able to try and research the products manufactured by the company, but they will not do this if they are not sure about the product. Before deciding to buy a product, consumers will compare the price of one product from one company with another company. The appropriate product price will encourage consumer decisions to buy the product. Saladbros is one of the most popular healthy food restaurants in Bali and in the end it is hoped that this brand image will influence consumer buying interest. The author uses quantitative methods with associative descriptive analysis. This study describes how much influence brand image has on consumer buying interest. It can be concluded that the researcher has determined 5 variables to be studied, namely promotion, product image, price, product quality and consumer purchase intention to describe how much influence the brand image has on consumer purchase interest in case studies at the Bali saladbros restaurant.